Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Mitogenomes of three Sinoxylon species and phylogenetic analysis of Bostrichoidea (Coleoptera) - Hua-Min Fan; Xiao-Yun Wang; Kai Lin; Qian Lu; Qiu-Hong Tao; Jun Li; Xia-Lin Zheng (Molecular Genetics and Genomics, 2026)

Particulate-to-molecule multiscale determinants of dewaterability of anaerobically digested biowaste - Yuanxin Li; Pinjing He; Hua Zhang; Fan Lü (Water Research, 2026)

Fate, toxicology and Organ-on-a-chip methodology of nanoplastics in human body - Yan Wang; Fan Lü; Jingjing Fang; Gang Li; Hua Zhang; Pinjing He (Toxicology, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Mixed conducting interlayer with self-regulating electronic/ionic conductivity for Li-metal solid state batteries - Ziwei Cai; Yang Li; Nan Zhang; Hua Jiang; Hai Zhong; Tao Peng; Jiangdong Fan; Xingjiang Liu; Andreu Cabot; Yaohua Mai (Chemical Engineering Journal, 2026)

Tire-derived antioxidants in terrestrial ecosystems: Occurrence, mechanistic toxicity, and sustainable mitigation strategies - Altaf Hussain; Xiu Fan; Kifayat Ullah; Avocegamou Serbin Armand; Tao Hua; Fengxiang Li (Bioresource Technology, 2026)

A pH-responsive bilayer film based on PHBV/ZnO and polyvinyl alcohol/carboxymethyl konjac glucomannan/alizarin was developed for monitoring and maintaining pork freshness - Qiu-Yu Peng; Meng Wang; Song Chen; Long-Hua Zou; Yun-Cheng Li; Fan-Bing Meng (Food Chemistry, 2026)

Resuspension of droplet residues from medical protective clothing: Effects of material properties, surface roughness, and initial droplet size - Xian Li; Huibo Qin; Nan Zhang; Liangyu Zhu; Fan Liu; Junzhou He; Wei Hua; Shifeng Zhao; Lingjie Zeng (Building and Environment, 2026)

Interference-reduced detection of 1,2-dihydroxybenzene using an acid-tolerant luminescent probe - Xinya Zhang; Ruibing Feng; Pengwei Zhang; Yu Fan; Shuyi Jia; Yao Tong; Dafeng Fang; Yu Wang; Hui Zhang; Qing-Wen Zhang; Huining Chai; Guodong Li; et al. (Analytica Chimica Acta, 2026)

DAF-16-dependent co-delivery of Lactobacillus acidophilus LA5 and schisandrin B via Spirulina platensis for glycolipid metabolic regulation and lifespan extension - Jingwen Xu; Yijie Li; Ning Guo; Chenyu Hua; Jiayi Gao; Jiaqi Wang; Guowei Shu; Fan Jiang; Jinyuan Sun; Guoliang Li (Food Bioscience, 2026)

Oral sunflower pollen-derived biomimetic delivery system for combined chemoimmunotherapy of colorectal cancer - Xin-Yue Xu; Meng Guan; Kai Cheng; Yong-Guo Hu; Li-Li Chen; Zi-Hui Yan; Jie Xiong; Dong Zhou; Jia-Hua Zou; Jin-Xuan Fan; Yuan-Di Zhao; Xiao-Shuai Zhang (Chemical Engineering Journal, 2026)

EPFR-mediated enhancement of atmospheric oxidants dominates the photochemical transformation of acenaphthylene on mineral dusts - Ying Hua; Ting Xue; Kanglu Li; Qin Ren; Shiyong Mou; Lvcun Chen; Fan Dong (ENGINEERING Environment, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

Nat10-mediated ac4C modification sustains macrophage proliferation and mitigates colitis progression via Mcm2 stabilization - Jinsong Wang; Tao Liu; Jiachen Zhao; Zhiqing Diao; Fuhong Fan; Demeng Qin; Yu Zhang; Xindi Wang; Ning Jiang; Chenbo Ding; Hua-Bing Li; Yuzhang Wu (Science China Life Sciences, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Constructing carbon-based perovskite solar cells based on the energy bands of perovskite synergistically optimized by graphite fluorinated polymers - Yulu Wang; Xiaoqin Fan; Enyu Liu; Hua Li; Qingbo Wei (Chemical Engineering Journal, 2026)

ANN-assisted interfacial engineering of MOFs heterostructures for synergistic CO2 photoreduction and antibiotic elimination - Fan Ye; Zhe Lin; Xu-Chao Xia; Ting Zou; Jin-Yu Dai; Lin Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2026)

Inhalation exposure and health risks of PM2.5-associated metals in a machinery plant: Probabilistic assessment and mask protection limits - Jianchao Ma; Fan Liu; Danting Luo; Xiaohong Zheng; Sujun Leng; Nianyong Zhou; Bingyuan Li; Hua Qian (Atmospheric Pollution Research, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Intensive management shifts litter decomposition from mycorrhizal to root-dominated pathway in a subtropical bamboo plantation - Wenhao Jin; Jiahe Wang; Jiangfei Ge; Xingcong Ma; Qifeng Wu; Shuai Shao; Chenfei Liang; Liyuan Peng; Xiaomin Ma; Yuchuan Fan; Yongfu Li; Junhui Chen; et al. (Applied Soil Ecology, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Genotypic features of Spinocerebellar Ataxia in Northern China: A Comparative Analysis with Southern China - Bin Chen; Songtao Niu; Xingao Wang; Yutin Ren; Fan Jian; Yuzhi Shi; Hongfei Tai; Hengheng Wang; Zhan Wang; Tao Cui; Wei Li; Hua Pan; et al. (The Cerebellum, 2026)

Drought trends and mitigation strategies in global urban areas based on a new comprehensive drought index - Beiqian Lei; Lei Li; Pak Wai Chan; Shaojia Fan; Hua Yuan; Yongjiu Dai (Sustainable Cities and Society, 2026)

Mitophagy activation for jawbone radiation injury therapy via angiogenesis/osteogenesis-active nanozymes - Tianxiao Wang; Weihua Shao; Ting Zhou; Yuchao Li; Ran Qin; Ziyu Chen; Jikang Cao; Xinyu Hu; Jingxuan Cang; Chang Sun; Yuli Wang; Huijun Jiang; et al. (Science China Life Sciences, 2026)

Adaptation-linked epigenetic variation and DNA methylation landscape across five populations of the marine economic fish Collichthys lucidus (Sciaenidae) - Li-Hua Jiang; Chang-Zhen Niu; Fan Fan; Xiao-Jun Yan (Hydrobiologia, 2026)

A calculation model on the minimum safe thickness of water-resisting rock mass for tunnel crossing active fault considering the fractal dimension and seismicity - Fan-meng Kong; Bing-hua Zhou; Xin Li; Zhao-di Han; Wen-song Wang (Applied Geophysics, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Intelligent compost maturity assessment: A hybrid computer vision and physicochemical parameters - Haojun Xie; Xueru Zhu; Chao Li; Fan Jiao; Xuebin Feng; Yiyun Zhang; Hua Li (Sustainable Chemistry and Pharmacy, 2026)

Aromatic distinctiveness of 'Beibinghong' wine driven by fungal succession and nitrogen metabolic flux under different fermentation strategies - Yujie Gao; Boyuan Fan; Yifan Zhou; Kai Hu; Hua Li; Hongyu Zhao (Food Bioscience, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Effects of Selenium-Enriched Lactobacillus plantarum on Production Performance, Egg Selenium Deposition, and Ovarian Antioxidant Function in Laying Hens During the Late Laying Period - Meilong Fan; Shurong Xie; Mengyu Zheng; Hua Zhou; Guanhong Li (Biological Trace Element Research, 2026)

Ultrasound-assisted purification of corncob xylooligosaccharides: Synergistic decolorization and citric acid removal - Jiakang Liang; Xingyu Fan; Jingyi Han; Haoxin Li; Ziwei Zhu; Li Chen; Xiaojie Yu; Hua Yang; Cunshan Zhou (Food and Bioproducts Processing, 2026)

Distribution characteristics and multi-factor driving mechanisms of perfluoroalkyl acids at lake inlets - Chenyu Tao; Jiasheng Li; Longyu Cheng; Jian Huang; Hua Zhang; Zihao Fan; Tao Luo (Environmental Geochemistry and Health, 2026)

Four new flavonoids from Sophora flavescens and their antibacterial activities - Yun Gao; Xin-Min Li; Fan-Fan Cao; Guo-Qing Long; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Terpenylated acetophenones from the root of Ferula ferulaeoides (Steud.) Korov. with selective cytotoxic activity - Yewen Jia; Wen Dang; Xueni Zhang; Yu Sun; Juan Zhang; Degang Qing; Congzhao Fan; Huiming Hua; Yingjie Wang; Ning Li (Phytochemistry, 2026)

Per-and poly-fluoroalkyl substances in lung tissues and their association with lung cancer - Xi-Ze Min; Li Ma; Fei Chen; Ying-Hua Hu; Chao Jiang; Yi-Fan Li; Yue Han; Zi-Feng Zhang; Kurunthachalam Kannan (Journal of Hazardous Materials, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Study on GPR Forward Modeling and Intelligent Identification of Subgrade Defects Characterized by Hidden Voids - Bin Wu; Yan-li Qi; Qi-guang Cheng; Fan-meng Kong; Yu-xuan Han; Yiguo Xue; Yue-hua Wu; Sheng-yong Dong; Ze-zhou Kang; Zhe Zhang; Yong-feng Shi; Min Han (Applied Geophysics, 2026)

Y/Ho ratios in marine sediments unveil Neoproterozoic ocean acidification - Yong-Sheng Liu; Wen-Shuai Li; Jun-Bo Zhang; Jie Lin; Ao Yang; Lian Zhou; Dai-Du Fan; Xi Zhu; Ying-Hua Zhang (Science Bulletin, 2026)

Longitudinal profiling of toxigenic fungi and mycotoxin risks in Coix lacryma-jobi L. - Anqi Xu; Yan Xu; Yuhui Yang; Fan Sun; Hua Cai; Yin Zhu; Xiaohui Xu; Xiushi Li; Aibo Wu; Na Liu (Journal of Hazardous Materials, 2026)

Competition release dominates growth recovery of four subtropical broadleaved tree species following an extreme snow event - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Shankar Panthi; Xin-Hua Peng; Ju-Mei Zhang; Pei-Li Fu; Ke-Yan Fang; Ze-Xin Fan (Forest Ecology and Management, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Experimental and Theoretical Investigations of Fatigue Mechanical Behavior of Transversely Isotropic Composite Rocks - Yu Song; Sheng-Qi Yang; Xiang-Xi Meng; Ke-Sheng Li; Yan-Hua Huang; Li-Feng Fan (Rock Mechanics and Rock Engineering, 2026)

Mitochondrial ORF188 confers salt stress tolerance in rapeseed via an ATP-dependent enhancement of antioxidant capacity - Shi-Hang Fan; Zi-Hong Huang; Jun Li; Xiang Ji; Wei Hua; Zheng-Wei Fu (Plant Cell Reports, 2026)

Magmatic control on the formation of the Diaoquan Ag-(Cu-Au) skarn deposit in the eastern North China Craton as revealed by zircon, apatite and sulfides - Gao-Hua Fan; Jian-Wei Li; Paul T. Robinson; Kai-Xuan Hui; Xiao-Dong Deng; Wen-Sheng Gao; Jin-Hao Liu; Hang-Jin Jiang (Mineralium Deposita, 2026)

Host-associated volatile cues drive foraging behavior of Trichopria drosophilae toward Drosophila suzukii-infested fruits - Hai-Kuan Sun; Fan Yang; Ze-Hua Wang; Ren Li; Guang-Hang Qiao; Qiu-Fei Li; Yu-Yu Wang; Shan-Ning Wang (Journal of Pest Science, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Nanocellulose hydrogel-based living materials: enhancing microbial biotransformation of lignocellulosic biomass - Xueyu Tang; Wei Hu; Zhiguo Wang; Yimin Fan; Yong Xu; Qiang Yong; Xin Li; Xia Hua (Bioresource Technology, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Estimating the steady and dynamic molecular fate of water treatment-derived dissolved organic matter - Junjie Qiu; Fan Lü; Xiao Hua; Jing Li; Hua Zhang; Qi Chen; Bin Xu; Pinjing He (Water Research, 2026)

Generation, transformation and inhibition mechanism of hazardous waste flue coated materials during copper smelting process - Kai Fan; Haipei Zhang; Zhongming Jiang; Songhe Ye; Zhenqin Ge; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Waste Management, 2026)

Substrate-driven enrichment and mining of ligninolytic bacteria for efficient lignin-to-PHA conversion - Tao Xu; Chong Han; He Liu; Zi-Yi Zhao; Fan-Li Zeng; Yu-Cheng Gu; Zhi-Hua Liu; Bing-Zhi Li (Chemical Engineering Journal, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Inhibitory effects of various lignocellulose pretreatment byproducts on xylonic acid biosynthesis by Gluconobacter oxydans - Fan Li; Shuiping Ouyang; Rui Zhang; Xia Hua; Yong Xu; Xin Zhou (Bioresource Technology, 2026)

Sucrose induces simultaneous autolysis attenuation and keratinase production enhancement in Bacillus subtilis WB600 - Yi-Ning He; Dao-Quan Jiao; Ge-Ge Chen; Xiao-Dong Pei; Zhi-Qiang Zhou; Fan Li; Yu-Hui Fang; Cheng-Hua Wang (Bioresource Technology, 2026)

CDGSH Iron Sulfur Domain 1 Relieves Neuronal Ferroptosis via Activating AMPK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

RRBP1 Inhibition Reduces Microglial M1 Polarization and Inflammation-Mediated Neuronal Loss and Oxidative Stress by Regulating ERK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Propofol attenuates angiogenesis by activating endoplasmic reticulum stress to suppress TFAP2C-driven VEGFA transcription - Fan Yang; Yi Liu; Hui Li; Xue Shang; Qing Hua; Yun Zhu; Beibei Tao; Zhirong Sun (Apoptosis, 2026)
During anesthesia, significant hemodynamic changes often alter the vascular microenvironment and affecting endothelial cell behavior. Propofol, a commonly used intravenous anesthetic, has been widely studied for its role in tumor angiogenesis through tumor cell–derived VEGF–mediated endothelial interactions. However, its direct effects on endothelial cell–mediated angiogenesis in non-malignant diseases such as diabetic retinopathy, diabetic nephropathy, and coronary heart disease remain unclear. To address this gap, we examined the effects of propofol on VEGFA-mediated angiogenesis in vitro and in vivo. Mechanistically, propofol triggers endoplasmic reticulum stress by promoting phosphorylation of PERK and its downstream effector eIF2α, leading to suppressed translation of TFAP2C—a transcription factor critical for endothelial function. Further analysis revealed that TFAP2C directly binds to the VEGFA promoter to activate its transcription, thereby facilitating VEGFA/VEGFR2-dependent angiogenesis. Together, these findings not only broaden the understanding of propofol’s pharmacological profile, but also identify TFAP2C as a novel transcriptional regulator of VEGFA, offering new perspectives for therapeutic targeting of VEGFA-mediated angiogenesis. Graphical abstract Schematic representation of the mechanism of propofol inhibition of VEGFA/VEGFR2-associated angiogenesis via the PERK/eIF2α/TFAP2C axis.

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

1-NP hijacks endocrine-metabolic checkpoints and disrupts testicular steroidogenesis by suppressing the cAMP-PKA-CREB-HMGCR axis - Xin-xin Zhu; Wei-wei Zhang; Ming-yue Hao; Zheng-ya Chen; Bai-fan Wan; Ming-hui Niu; Xiu-liang Li; Jian-hua Wei; Su-ya Liu; Shuang-ling Mi; Hua Wang; De-xiang Xu; et al. (Toxicology Letters, 2025)

From sediment sinks to ice sinks: Differential phase partitioning of PAH derivatives in a cold-climate aquatic ecosystem - Bo Meng; Nan Jiang; Xin-Ming Guo; Jie Hu; Danilova Sakhayana Nikolaevna; Zakharov Moisei Ivanovich; Yi-Fan Li; Zi-Feng Zhang; Zhong-Hua Tang (Environmental Research, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Luminescence dating of lava-baked sediments constraints on the high frequency of Holocene eruptions in the Tengchong volcanic field, southwestern China - Chang Huang; Chunxin Wang; Anchuan Fan; Sheng-Hua Li (Science China Earth Sciences, 2025)

Predictive value of serum lipid for kawasaki disease shock syndrome: a prospective study - Ping Wu; Bowen Li; Jinlin Wu; Yunhao Li; Fan Ma; Nanjun Zhang; Xiaoliang Liu; Yimin Hua; Kaiyu Zhou; Chuan Wang; Hongyu Duan; Shuran Shao (Immunologic Research, 2025)

Characterization of 4-coumarate CoA ligase (4CL) gene family and functional study of Sm4CL2/3/7/9 in Salvia miltiorrhiza - Fan Fu; Huiting Qin; Yujie Xin; Qianmo Li; Heng Kang; Limin Han; Wenping Hua; Xiaoyan Cao (Functional & Integrative Genomics, 2025)

Progress in the application of DIC technology to rock mechanics testing: a review - Hao-fan Luo; Yang Tang; Wen-tao Feng; Jian-feng Liu; Hua Li; En-ze Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

Matrine as a potent inhibitor of canine mammary tumors: Insights from network pharmacology, molecular docking, molecular dynamics and in vitro analysis - Fida Noor; Wenwen Ding; Na Sun; Panpan Sun; Huizhen Yang; Hua Zhang; Kuohai Fan; Wei Yin; Zhenbiao Zhang; Yaogui Sun; Jianzhong Wang; Jia Zhong; et al. (Veterinary Immunology and Immunopathology, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Carbon and nitrogen footprints of Northern Chinese sheep and goat in the context of “Carbon Neutrality” - Fan Jiao; Zhenyu Liu; Hua Li (Livestock Science, 2025)

Revisiting the genesis of Bi-Te-Au-S associations: Implications for the ore-forming processes in gold deposits - Gao-Hua Fan; Jian-Wei Li; Zhan-Ke Li; Xue-Feng Yu; Xiao-Dong Deng; Jin-Hao Liu; Hang-Jin Jiang; Hong-Jun Sun; Tian-Ming Zhang (Chemical Geology, 2025)

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

Rapid and highly sensitive mass spectrometric detection of n-alkanes via a novel photoionization-induced nitrogen dioxide cation chemical ionization source - Baimao Zhang; Bo Li; Lei Hua; Zhigang Fan; Guolong Wang; Hang Li; Heng Wang; Xiaopeng Li; Jichun Jiang; Haiyang Li (Analytica Chimica Acta, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

The role of potassium in lode gold mineralization: insights from ab initio molecular dynamics and geochemical modeling - Gao-Hua Fan; Jian-Wei Li; Yuan Mei; Si-Yu Hu; Ri-Chen Zhong; Chang Yu; Xiao-Dong Deng; Hao Cui; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

ROS-scavenging microspheres loaded with electromagnetically enhanced small extracellular vesicles for advanced osteoarthritis therapy - Hongqi Zhao; Yang Fan; Xuan Fang; Hongliang Li; Tao Xu; Jian Li; Guangzi Chen; Gaohong Sheng; Hua Wu; Wei Seong Toh; Chaoxu Liu; Tianqi Wang; et al. (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Fe-C micro-electrolysis supercharged EGSB: Breaking toxicity barriers in waste acid condensate treatment for maximum COD/NH3-N and H2S control - Yanhe Han; Xueao Li; Hao Yao; Fan Zhao; Naif Abdullah Al-Dhabi; Qingpeng Zhao; Mengxiang Wei; Zhi Guo; Hua Ji; Lei Zhang; Wangwang Tang; Xuejiao Ma (Journal of Water Process Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Berberine attenuates the expression of NLRP3 and downstream inflammasome effectors in diabetic retinopathy - Na Li; Ji-Lin Chen; Yi-Jian Sun; Jia-Fan Sun; Ting-Hua Wang; Amy Yi Hsan Saik; Alan Han-Kiat Ong (Journal of Natural Medicines, 2025)

New anti-inflammatory limonoids from the fruits of Melia azedarach - Fan Cao; Jin-Huang Shen; Zhi-Jun Li; Wen-Lu Wang; Zhen-Wei Chen; Yong-Hong Zhang; Xin-Hua Ma (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved satellite-scale land surface temperature components retrieval with hotspot effect correction and temperature difference constraints - Yifan Lu; Zunjian Bian; Jean-Louis Roujean; Hua Li; Frank M. Göttsche; Yajun Huang; Tengyuan Fan; Biao Cao; Yongming Du; Qing Xiao (Remote Sensing of Environment, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunology, 142: 109,134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Halogens-co-mixing strategy for the elucidation of halogen effect in copper-based hybrid luminescent materials - Jialin Zhu; Chen Su; Jiali Fan; Haibo Li; Hua Tong; Wei Liu; Gangfeng Ouyang (Chemical Engineering Journal, 2025)

Mitochondria derived from human embryonic stem cell-derived mesenchymal stem cells alleviate the inflammatory response in human gingival fibroblasts - Bicong Gao; Chenlu Shen; Kejia Lv; Xuehui Li; Yongting Zhang; Fan Shi; Hongyan Diao; Hua Yao (Journal of Zhejiang University-SCIENCE B, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa by product as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunol. (2023) 142 109134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Impact of COVID-19 pandemic on air pollution and hospitalization risk for cardiovascular and respiratory diseases in Suzhou, China - Fan Liu; Xikun Liu; Shuhua Yu; Xiang Liu; Jingguang Li; Chongyang Zhang; Chanjuan Sun; Hua Qian; Xinyi Zhu (Atmospheric Pollution Research, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Advancements in chain elongation technology: Transforming lactic acid into caproic acid for sustainable biochemical production - Minyu Suo; Lingxiu Liu; Hongye Fan; Nan Li; Hua Pan; Dzmitry Hrynsphan; Savitskaya Tatsiana; Raúl Robles-Iglesias; Zeyu Wang; Jun Chen (Bioresource Technology, 2025)

White matter microstructural and cognitive function changes in bipolar depression patients with suicidal ideation - Junfan Liang; Rui Fan; Xinyin Guo; Hua Liu; Xuehua Li; Jixiang Yuan; Kezhi Liu; Xuemei Liang; Bo Xiang (Brain Imaging and Behavior, 2025)

Cytotoxic metabolites from the mangrove endophytic fungus Aspergillus sp. GXNU QG1a - Xianglong Bo; Yufei Zhao; Feng Qin; Furong Wu; Meijing Tan; Shichao Ju; Zishuo Song; Wenjun Li; Fan He; Youquan Wei; Hua Xu; Xishan Huang (Natural Product Research, 2025)

Proteome profiling of the lung tissues of the mice co-infected with H9N2 influenza A virus and Pseudomonas aeruginosa - Sun Ying-Li; Fan Hua; Li Wen-qian; Li Dan; Bai Ke-fei; Dong Lu-jiao; Zhang Hui-ning; Li Jian-liang; Xie Zhi-jing (Veterinary Microbiology, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Chaihu Guizhi Ganjiang Decoction ameliorates chronic pancreatitis by modulating the SK1/S1P signaling pathway - Guo-Wang Yao; Cai-Xia Li; Yu-Xing Fan; Yu-Zhen Zhuo; Shu-Kun Zhang; Li-Hua Cui (Journal of Natural Medicines, 2025)

A damage constitutive model for cemented sandy gravel materials - Qin Yuyang; Li Guoying; Ling Hua; Xu Jiangtao; Fan Kaifang (Bulletin of Engineering Geology and the Environment, 2025)

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Mineralogy, geochemistry, and S isotope investigation of seafloor massive sulfides from the Yunzang hydrothermal field, South Atlantic Ridge - Wen-Sheng Li; Pei Ni; Xue-Fa Shi; Bing Li; Shao-Wen Liu; Stefano Albanese; Fei-Peng Fan; Guan-Hua Wang; An-Qi Hong (Journal of Geochemical Exploration, 2025)

Novel N-deficient g-C3N4 /Ni(OH)2 2D heterojunction design for efficient photocatalytic H2 evolution - Xue Bai; Tao Yang; Manqing Zhao; Hua Fan; Chao Li; Enzhou Liu (Journal of Environmental Chemical Engineering, 2025)

Global analysis of fungal biosynthetic gene clusters reveals the diversification of diketopiperazine biosynthesis - Bin Wei; Ti-Ti Ying; Hua-Wei Lv; Zhen-Yi Zhou; Hai Cai; Gang-Ao Hu; Hui-Min Liang; Wen-Chao Yu; Yan-Lei Yu; Ai-Li Fan; Kui Hong; Xing-Nuo Li; et al. (Bioresource Technology, 2025)

A new ensemble learning method based on signal source driver for GNSS coordinate time series prediction - Jian Wang; Zhao Li; Wenlan Fan; Weiping Jiang; Qusen Chen; Hua Chen (GPS Solutions, 2025)

Efficient conversion and highly sensitive detection of PAEs in milk based on hydrazinolysis reaction and hydrogen bonding using SERS technique - Lili Hua; Hongmei Li; Jing-Wen Zhou; Xiao-Feng Liu; Xian-Ming Guo; Zhao-Bing Zhang; Yichuan Kou; Tang-Tang Xie; Cuihong Sheng; Lin Zhang; Sheng-Hong Liu; Fan-Li Zhang; et al. (Analytica Chimica Acta, 2025)

OncomiR mdv1-miR-M7-5p promotes avian lymphomatosis by modulating the BCL2/Bax mitochondrial apoptosis signaling pathway - Jun Zhou; Fan Yang; Congsen Zheng; Yanting Chen; Meiting Chen; Qiaoer Lin; Chuanzhe Chang; Shikai Cai; Zhaoyang Sun; Hua Li; Limei Qin; Yanfeng Chen (Veterinary Microbiology, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Electrocatalytic reduction of nitrate to ammonia on CoMoO4 microspheres: A comparative study with Co3O4 - Yibo Xu; Long Cao; Hele Hua; Rui Li; Yunfang Wang; Jianxin Liu; Yawen Wang; Caimei Fan (Chemical Engineering Journal, 2025)

Reinforced Collaborative-Competitive Representation for Biomedical Image Recognition - Junwei Jin; Songbo Zhou; Yanting Li; Tanxin Zhu; Chao Fan; Hua Zhang; Peng Li (Interdisciplinary Sciences: Computational Life Sciences, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Petrogenesis and geodynamic mechanism of Early Miocene post-collisional ultrapotassic rocks in the eastern Lhasa Terrane, southern Tibet - Chenyuan Hua; Feng Huang; Song Zhang; Haiyan Fan; Yunchuan Zeng; Mingjian Li; Shuo Wang; Xi Chen; Jing Hu; Jifeng Xu (Lithos, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Amine antioxidants in water, ice, sediment and soil from the Songhua Wetland, Northeast China: Occurrence and fate - Jie Hu; Tian-Wei Xu; Ye Zhang; Meng-Yuan Xiao; Bo Meng; Vasiliy Egorovich Kolodeznikov; Natalia Nikolaevna Petrova; Vasilii Vasilevich Mukhin; Zi-Feng Zhang; Zhong-Hua Tang; Yi-Fan Li (Science of The Total Environment, 2025)

Life cycle assessment of small-scale incineration facilities: Reducing environmental burdens in underdeveloped areas - Nanlin Liao; Fan Lü; Xiaojing Li; Hua Zhang; Pinjing He (Journal of Cleaner Production, 2025)

A critical review of in-situ moisture distribution detection and characterization techniques utilizing deep dewatering for organic waste - Yuanxin Li; Pinjing He; Hua Zhang; Fan Lü (Journal of Environmental Management, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Metagenomic Analysis of Gut Microbiome of Persistent Pulmonary Hypertension of the Newborn - Linli Han; Chuyang Lin; Yue Lan; Yimin Hua; Jinlin Wu; Zhenxin Fan; Yifei Li (Cardiovascular Toxicology, 2025)

Di-(2-ethylhexyl) Phthalate Exposure Induces Developmental Toxicity in the Mouse Fetal Heart via Mitochondrial Dysfunction - Yafei Guo; Bowen Li; Yu Yan; Nanjun Zhang; Shuran Shao; Lixia Yang; Lixue Ouyang; Ping Wu; Fan Ma; Hongyu Duan; Kaiyu Zhou; Yimin Hua; et al. (Cardiovascular Toxicology, 2025)

Comparative evaluation and QSAR modeling of developmental neurotoxicity of novel brominated flame retardants in zebrafish - Fan Li; Lei Lei; Yuxi Zhou; Xiaochen Wang; Yindan Zhang; Jianghuan Hua; Jian Han; Lihua Yang; Bingsheng Zhou (Science of The Total Environment, 2024)

Dust event identification and characterization with one-year online observations in Beijing - Feixue Zheng; Jinwen Li; Chenjie Hua; Jiali Xie; Yusheng Zhang; Liye Li; Sunan Shen; Simo Hakala; Chao Yan; Zemin Feng; Xiaolong Fan; Federico Bianchi; et al. (Science of The Total Environment, 2024)

Metabolomics combined with physiology reveal how white clover (Trifolium repens L.) respond to 6PPD stress - Jian-Xin Wang; Ye Zhang; Jie Hu; Yi-Fan Li; Kolodeznikov Vasiliy Egorovich; Petrova Natalia Nikolaevna; Mukhin Vasilii Vasilevich; Zi-Feng Zhang; Zhong-Hua Tang (Science of The Total Environment, 2024)

Variation in the Quaternary Stegodon-Ailuropoda Faunal Complex in Southern China: Upper Pubu Cave (Bubing Basin, Guangxi) - Yijing Zhang; Yaobin Fan; Yanyan Yao; Chun Tian; Hua Liang; Jinyan Li; Wei Liao; Christopher J. Bae; Wei Wang (Quaternary Science Reviews, 2024)

Co-existence of airborne SARS-CoV-2 infection and non-infection in three connected zones of a restaurant - Wei Jia; Qun Wang; David Christopher Lung; Pak-To Chan; Peihua Wang; Edwin Chung-Hin Dung; Tiffany Didik; Garnet Kwan-Yue Choi; Herman Tse; Yijie Wu; Te Miao; Wenzhao Chen; et al. (Journal of Hazardous Materials, 2024)

High-affinity potassium transporter TaHAK1 implicates in cesium tolerance and phytoremediation - Jin Liu; Shuai-Bo Chen; Ze-Hua Fan; Haitao Liu; Yinglong Chen; Chandra Shekhar Seth; Evgenios Agathokleous; Tian-Cai Guo; Guo-Zhang Kang; Ge-Zi Li (Journal of Hazardous Materials, 2024)

Ferulic acid triggering a co-production of 4-vinyl guaiacol and fumaric acid from lignocellulose-based carbon source by Rhizopus oryzae - Xueyu Tang; Shanshan Wu; Xia Hua; Yimin Fan; Xin Li (Food Chemistry, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Nanoparticle attachment promotes nugget effect of Au-rich metallic melts in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ya-Fei Wu; Si-Yu Hu; Xiao-Dong Deng; Hao-Yang Zhou; Zhan-Ke Li; Yan Liu (Contributions to Mineralogy and Petrology, 2024)

Suppression of seismic random noise by deep learning combined with stationary wavelet packet transform - Hua Fan; Dong-Bo Wang; Yang Zhang; Wen-Xu Wang; Tao Li (Applied Geophysics, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Life-time exposure to decabromodiphenyl ethane (DBDPE) caused transgenerational epigenetic alterations of thyroid endocrine system in zebrafish - Yumiao Sun; Xiaochen Wang; Wei Guo; Fan Li; Jianghuan Hua; Biran Zhu; Yongyong Guo; Jian Han; Lihua Yang; Bingsheng Zhou (Science of The Total Environment, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Research and application of joint-constrained inversion of transient electromagnetic multivariate parameter - Jian-lei Guo; Yan-wei Hou; Xiong-wei Li; Zhi-peng Qi; Ke-rui Fan; Wen-han Li; Wei-hua Yao; Xiu Li (Journal of Applied Geophysics, 2024)

Fabrication of V2O3-TiO2-rGO ternary heterojunction composite to enhance the hydrogen storage performance of MgH2 - Ziqi Liu; Hua Ning; Ruojiang Liu; Sizhi Ding; Jiakun Yang; Yuanxin Tan; Yi Fan; Renhuan Li; Peilin Qing; Haizhen Liu; Jin Guo; Zhiqiang Lan (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Anti-adipogenesis and anti-obesity potential of alliin mediated by modulating glycolipid metabolism via activating PPARγ signaling - Ming-Yan Yang; Yu-Jing Liu; Mei-Hua Zheng; Tao Pan; Zhen-Yuan Li; Bai-Fang Gong; Hua-Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Suppressed testicular macrophage M1 polarization by HDAC5 enforces insensitivity to LPS-elicited blood-testis barrier damage - Hao Li; Yi-Fan Hu; Xin-Run Wang; Kong-Wen Ouyang; Hua Wang; Kai-Wen Wang; Wei Chang; Jin Zhang; Zhi Yuan; Yong-Wei Xiong; Hua-Long Zhu; Lan Yang; et al. (Food and Chemical Toxicology, 2024)

LPAR6 Participates in Neuropathic Pain by Mediating Astrocyte Cells via ROCK2/NF-κB Signal Pathway - Xiaoyi Fan; Ruitong Chu; Xin Jiang; Peng Ma; Yan Chu; Tong Hua; Mei Yang; Ruifeng Ding; Jian Li; Zhenghua Xiang; Hongbin Yuan (Molecular Neurobiology, 2024)

Multi-dimensional signals coupling of simultaneous acquisition stripping current with laser-induced breakdown spectroscopy for accurate analysis of Cd(II) in coexisting Cu(II) - Yuan-Fan Yang; Zong-Yin Song; Zi-Hao Liu; Zhi-Wei Gao; Xin Cai; Cong-Cong Huang; Pang-Da Dai; Meng Yang; Pei-Hua Li; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

Chemical constituents from the roots of Dolomiaea souliei - Zhe Wang; Li-Dan Zhang; Gang-Gang Zhou; Qi-Zheng Zhong; Yun-Bin Jiang; Guo-Wei Wang; Zhi-Hua Liao; Fan-Cheng Meng; Min Chen (Natural Product Research, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Properties, extraction and purification technologies of Stevia rebaudiana steviol glycosides: A review - Chengxia Huang; Yang Wang; Cunshan Zhou; Xingyu Fan; Qiaolan Sun; Jingyi Han; Chenhui Hua; Yao Li; Yunwei Niu; Clinton Emeka Okonkwo; Deyang Yao; Linglin Song; et al. (Food Chemistry, 2024)

High-throughput screening of 222 pesticides in road environments in a megacity of northern China: A new approach to urban population exposure - Ye Zhang; Jin-Nong Li; Jian-Xin Wang; Yi-Fan Li; Roland Kallenborn; Hang Xiao; Ming-Gang Cai; Zhong-Hua Tang; Zi-Feng Zhang (Environmental Research, 2024)

Chromones and biflavonoids from Garcinia pedunculata and Garcinia nujiangensis and their anti-inflammatory activity - Xiaojie Fan; Jiaxin Guo; Dongyan Feng; Dahong Li; Huiming Hua (Phytochemistry, 2024)

A new photoionization-induced substitution reaction chemical ionization time-of-flight mass spectrometry for highly sensitive detection of trace exhaled ethylene - Baimao Zhang; Lei Hua; Zhigang Fan; Yuxuan Wen; Lichuan Zhang; Yuanyuan Xie; Yunnan Gao; Jichun Jiang; Haiyang Li (Analytica Chimica Acta, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Transforming crystal structures of cobalt molybdate to generate electron-rich sites for electrochemical detection of Pb(II) - Yang-Zhi Liu; Xin Cai; Cong-Cong Huang; Zi-Hao Liu; Yuan-Fan Yang; Yong-Yu Li; Meng Yang; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

Enzyme-free and rapid colorimetric analysis of osteopontin via triple-helix aptamer probe coupled with catalytic hairpin assembly reaction - Qin Weng; Hang Li; Zhichao Fan; Yan Dong; Yuchen Qi; Peilin Wang; Cheng Luo; Jianjun Li; Xiang Zhao; Hua Yu (Analytica Chimica Acta, 2024)

Thermostability-assisted limited proteolysis-coupled mass spectrometry for capturing drug target proteins and sites - Liu Yang; Chen-Wan Guo; Qi-Ming Luo; Zi-Fan Guo; Ling Chen; Yasushi Ishihama; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2024)

Reconstructing the trade history: provenance study of Han bronze mirrors in and out of Han China - Xiang Wang; Ruiliang Liu; Jun Gao; A. Mark Pollard; Anchuan Fan; Fang Huang; Ruiliang Li; Shixuan Zhang; Fenglin Hua; Zhengyao Jin (Archaeological and Anthropological Sciences, 2024)
A rapidly increasing number of bronze mirrors dated to the Chinese Han dynasty (202 BC – AD 220), known for their unique decorative patterns and highly developed alloying techniques, have been widely discovered in both China and beyond, providing fresh materials and scientific data to revisit their geological provenance, production and circulation network along the ancient Silk Road. In this paper, 47 bronze mirrors unearthed in the southeastern provinces of China, including Zhejiang, Anhui and Fujian provinces, have been characterized by typo-chronology, lead isotopic analysis, compositional analysis and metallography. A much wider comparative study is also carried out through a combination of data from China, Japan, Central Asia, and Southeast Asia, leading to a more updated lead isotopic database of the Han mirrors spreading out of China in various directions. Compared with the traditional ‘optimal’ model based on the Han mirrors recovered in Japan, the current study contributes several key changes in the bronze mirror production of the Han dynasty. The systematic analysis of the alloy composition, trace elements and typological studies shows that the bronze mirror industry shifted towards a more standardized production in the middle to late Western Han Dynasty. In contrast to the substantial change of non-mirror bronze productions, the similar distribution of lead isotope data in early and middle to late Western Han mirrors suggests that the ‘official monopoly of salt and iron’ policy was less effective for the management of lead involved in mirror production. Bronze mirrors dated to middle to late Western Han discovered outside Han-China, such as Japan, Thailand, Afghanistan, Xiongnu and the ancient Dian Kingdom, appear to be subjected to a more specific type of lead as a result of the state-centralized policy of the Western Han court.

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

m6A-methylated Lonp1 drives mitochondrial proteostasis stress to induce testicular pyroptosis upon environmental cadmium exposure - Kong-Wen Ouyang; Tian-Tian Wang; Hua Wang; Ye-Xin Luo; Yi-Fan Hu; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Yong-Wei Xiong; Jin Zhang; Wei Chang; Yu-Feng Zhang; et al. (Science of The Total Environment, 2024)

GPX4 degradation contributes to fluoride-induced neuronal ferroptosis and cognitive impairment via mtROS-chaperone-mediated autophagy - Pu Zhao; Quan Yuan; Chen Liang; Yilu Ma; Xiaoying Zhu; Xueqin Hao; Xinyu Li; Jian Shi; Qizhi Fu; Hua Fan; Dongmei Wang (Science of The Total Environment, 2024)

The De underestimation caused by the unstable medium component in the initial OSL signal from lava-baked quartz and correction strategies - Chun-Xin Wang; Chang Huang; Anchuan Fan; Sheng-Hua Li (Quaternary Geochronology, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Catalytic diesel soot combustion over FeCo2O4 monolithic catalysts with different morphologies - Zhenhai Fan; Hua Yang; Feiyang Qin; Jieyu Xiao; Hui Xian; Xingchuan Yang; Yi Yu; Guoji Liu; Li Xu; Chunmei Cao (Journal of Environmental Chemical Engineering, 2024)

Clinical Characteristics and Pathogen Spectrum of Male Genital Fungal Infections in Nanchang Area, South China - Yun Jin; Yangmin Gao; Yunpeng Luo; XiaoHua Tao; Qing Jiang; Xinyi Fan; Rui Xu; Hua Qian; Xiaoguang Li; Zhijun Zhou (Mycopathologia, 2024)
The cutaneous fungal infections in male genitalia are relatively rare, and often present with various atypical clinical symptoms. It was mainly reported in a small number of case reports, while data with large number of patients were rarely reported. In this study, we reported 79 male patients with cutaneous fungal infections on scrotum or penis. The fungal infections were confirmed by microscopic examination directly and fungus culture. Clinical characteristics and predisposing factors were also collected. Of these 79 patients, 72 has lesions on scrotum, 5 on penis and 2 on both scrotum and penis. Trichophyton (T.) rubrum is the most common pathogen, found in 50 (67.6%) patients, which presented diverse clinical manifestation such as majorly erythematous, dry diffused scaly lesions without a clear border, slightly powdery and scutular scalings. Candida (C.) albicans is the secondly common pathogen, found in 21 (28.4%) patients, which also presented diverse lesions such as erythematous with dry whitish scaly lesions and erythematous erosion. The predisposing factors mainly included concomitant fungal infections on sites other than genitalia, especially inguinal region (tinea cruris), application of corticosteroid and high moisture. In conclusion, cutaneous fungal infections in male genitalia could be caused by different fungi, showed atypical or mild clinical appearances in most cases and might be a fungus reservoir, emphasizing the necessity to timely perform the fungi examinations and corresponding therapy.

The impact of elevated CO2 concentration on photosynthesis, growth and hydraulics of evergreen and deciduous tree seedlings from a subtropical forest in Southwest China - Pei-Li Fu; Ya Zhang; Jin-Hua Qi; Yong-Jiang Zhang; Guang-You Hao; Patrick M. Finnegan; Qiao-Shun Yan; Ze-Xin Fan (Agricultural and Forest Meteorology, 2024)

Accurate prediction bioaccessibility of PAHs in soil-earthworm system by novel magnetic solid phase extraction technique - Yu-Han Fan; Shi-Bin Qin; Xiao-Xuan Mou; Xiao-Shui Li; Shi-Hua Qi (Chemosphere, 2024)

Aniline antioxidants in road dust, parking lot dust, and green-belt soil in Harbin, a megacity in China: Occurrence, profile, and seasonal variation - Ye Zhang; Jin-Nong Li; Jian-Xin Wang; Jie Hu; Jia-Lin Sun; Yi-Fan Li; Wen-Long Li; Zhong-Hua Tang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Growth, biofilm formation, and motility of Listeria monocytogenes strains isolated from food and clinical samples located in Shanghai (China) - BinRu Gao; Hua Cai; Biyao Xu; Fan Yang; Xin Dou; Qingli Dong; Hui Yan; Xiangfeng Bu; Zhuosi Li (Food Research International, 2024)

Geographical traceability of soybean: An electronic nose coupled with an effective deep learning method - Huaxin Sun; Zhijie Hua; Chongbo Yin; Fan Li; Yan Shi (Food Chemistry, 2024)

Cadmium exposure induced neuronal ferroptosis and cognitive deficits via the mtROS-ferritinophagy pathway - Dongmei Wang; Yiran Wu; Xiang Zhou; Chen Liang; Yilu Ma; Quan Yuan; Ziyue Wu; Xueqin Hao; Xiaoying Zhu; Xinyu Li; Jian Shi; Junliang Chen; et al. (Environmental Pollution, 2024)

Rutin alleviates lupus nephritis by inhibiting T cell oxidative stress through PPARγ - Tongtong Yi; Wei Zhang; Ying Hua; Xingpan Xin; Zhenyu Wu; Ying Li; Chengping Wen; Yongsheng Fan; Jinjun Ji; Li Xu (Chemico-Biological Interactions, 2024)

Integrated microbiome and metabolome analyses reveal the effects of low pH on intestinal health and homeostasis of crayfish (Procambarus clarkii) - Zhanqi Wang; Jiapeng Li; Pengfei Zhao; Zaihang Yu; Lianlian Yang; Xueyan Ding; He Lv; ShaoKui Yi; Qiang Sheng; Liqin Zhang; Fan Zhou; Hua Wang (Aquatic Toxicology, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

Mg-Fe bimetallic oxide nanocomposite for superior phosphate removal and recovery from aquatic environment: Synergistic effects of sorption and struvite crystallization - Sheng-Hui Yu; Yan Wang; Li Hua; Mei-Ying Fan; Xin-Hao Ren; Lei Zhang (Journal of Environmental Chemical Engineering, 2024)

Combination of chemometrics and mass spectrometric methods for the data mining of molecular structure information of coal and biomass - Guo-Sheng Li; Xing Bai; Min-Hua Wang; Xing Fan; Xiao-Yan He; Yierxiati Dilixiati; Xian-Yong Wei; Hai-Xu Zou; Guligena Pidamaimaiti (Fuel, 2024)

Long Non-Coding RNA MALAT1 Protects Against Spinal Cord Injury via Suppressing microRNA-125b-5p Mediated Microglial M1 Polarization, Neuroinflammation, and Neural Apoptosis - Yuanlong Li; Hua Fan; Xiong Han; Jun Sun; Ming Ni; Xiaodan Hou; Fengqin Fang; Wei Zhang; Peizhi Ma (Molecular Neurobiology, 2024)

On the contributions of refined thermal expansion model to nonlinear variations in different GNSS height time series products - Ran Lu; Zhao Li; Qusen Chen; Xin Ding; Kaichun Yang; Mingyuan Zhang; Yang Lu; Wenlan Fan; Hua Chen; Weiping Jiang (GPS Solutions, 2024)

Novel material-oriented valorization of biogas can achieve more carbon reduction than traditional utilization by bioelectricity or biomethane - Jing Guo; Pinjing He; Hao Wu; Yonglan Xi; Chao Li; Hua Zhang; Jun Zhou; Jingwen Liao; Fan Lü (Bioresource Technology, 2024)

Cathepsin B degrades RbcL during freezing-induced programmed cell death in Arabidopsis - Gang Yang; Tao Chen; Ting-ting Fan; Xiang-yu Lin; Yu-qiong Cui; Wei-chao Dong; Li-zhe An; Hua Zhang (Plant Cell Reports, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

Greenhouse gas emissions of municipal solid waste in Shanghai over the past 30 years: Dependent on the dynamic waste characteristics and treatment technologies - Xiaojing Li; Fan Lü; Nanlin Liao; Hua Zhang; Na Yang; Pinjing He (Resources, Conservation and Recycling, 2024)

An analytical urban temperature model with building heterogeneity using geometric optical theory - Zunjian Bian; Tengyuan Fan; J.-L. Roujean; Dandan Wang; Mark Irvine; Shengbiao Wu; Biao Cao; Hua Li; Yongming Du; Qing Xiao; Qinhuo Liu (Remote Sensing of Environment, 2024)

Scutellarin targets Wnt5a against zearalenone-induced apoptosis in mouse granulosa cells in vitro and in vivo - Na Sun; Abdul Haseeb; Panpan Sun; Hua Zhang; Jia Zhong; Wei Yin; Kuohai Fan; Huizhen Yang; Zhenbiao Zhang; Yaogui Sun; Panpan Hu; Hongquan Li (Journal of Hazardous Materials, 2024)

Synergistic activation of P and orbital coupling effect for ultra-sensitive and selective electrochemical detection of Cd(II) over Fe-doped CoP - Zhi-Wei Gao; Yong-Yu Li; Pei-Hua Li; Yuan-Fan Yang; Yong-Huan Zhao; Meng Yang; Shi-Hua Chen; Zong-Yin Song; Xing-Jiu Huang (Journal of Hazardous Materials, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Diagenetic effects on strontium isotopes in shallow-water carbonate sediments from Middle Miocene to Recent - Xinran Chen; Mengchun Cao; Thomas J. Algeo; Na Li; Guang-yi Wei; Yi-bo Lin; Hua Zhang; Lei Xiang; Youhua Zhu; Changgui Xu; Caiwei Fan; Shuzhong Shen; et al. (Chemical Geology, 2024)

Total utilization of lignocellulosic biomass with xylooligosaccharides production priority: A review - Xingyu Fan; Manni Ren; Cunshan Zhou; Fangong Kong; Chenhui Hua; Olugbenga Abiola Fakayode; Clinton Emeka Okonkwo; Haoxin Li; Jiakang Liang; Xue Wang (Biomass and Bioenergy, 2024)

Melatonin decreases GSDME mediated mesothelial cell pyroptosis and prevents peritoneal fibrosis and ultrafiltration failure - Hongxia Ruan; Xuejuan Li; Lina Zhou; Zihan Zheng; Rulin Hua; Xu Wang; Yuan Wang; Yujie Fan; Shuwen Guo; Lihua Wang; Shafiq ur Rahman; Ziwei Wang; et al. (Science China Life Sciences, 2024)

Regulation of Hepatocellular Cholesterol Metabolism By Lactobacillus Paracasei BY2 and Its Embedding Delivery - Hua-Ling Cui; Meng-Fan Li; Sheng-Ya Liu; Ming Yu; Wen-Yong Lou (Probiotics and Antimicrobial Proteins, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Leaching of biochar at different stages of anaerobic digestion: Leaching behaviors, leachate chemodiversity and effects - Haohao Zhang; Qi Chen; Hua Zhang; Pinjing He; Shasha Li; Fan Lü (Journal of Cleaner Production, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Efficacy of bioaugmentation with nondomesticated mixed microbial consortia under ammonia inhibition in anaerobic digestion - Chao Li; Fan Lü; Wei Peng; Pinjing He; Hua Zhang (Bioresource Technology, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

NLRP3 inflammasome-mediated pyroptosis involvement in cadmium exposure-induced cognitive deficits via the Sirt3-mtROS axis - Dongmei Wang; Yiran Wu; Shihao Sun; Pu Zhao; Xiang Zhou; Chen Liang; Yilu Ma; Sanqiang Li; Xiaoying Zhu; Xueqin Hao; Jian Shi; Hua Fan (Science of The Total Environment, 2023)

Moderate selenium alleviates the pulmonary function impairment induced by cadmium and lead in adults: A population-based study - Heze Fan; Ying Xiong; Yuzhi Huang; Lijun Wang; Chenbo Xu; Wenyuan Li; Xueying Feng; Yuxuan Yang; Rui Hua; Zihao Wang; Zuyi Yuan; Juan Zhou (Science of The Total Environment, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

Multi-objective global dynamic optimal scheduling of smart building loads considering carbon emissions - Lingzhi Yi; Huiting Zhang; Yahui Wang; Bote Luo; Lv Fan; Jiangyong Liu; Guang hua Li (Energy and Buildings, 2023)

Novel amino-modified bamboo-derived biochar-supported nano-zero-valent iron (AMBBC-nZVI) composite for efficient Cr(VI) removal from aqueous solution - Xiaobin Zhou; Yingxue Wang; Huili Liu; Yanan Zhang; Yinming Fan; Shengpeng Mo; Huaxia Li; Junyi Wang; Hua Lin (Environmental Science and Pollution Research, 2023)

Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei) - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Long-term anthropogenic field management enhanced wheat productivity and resource utilization in the Loess Plateau region of China - Peng Wu; Gang Zhao; Qi Wu; Hua Huang; Peng Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; Shangzhong Li; Lei Wang; Wanli Cheng; Jian Fu; et al. (European Journal of Agronomy, 2023)

Robust historical and future drying trends in Central Asia evidenced by the latest observation and modeling datasets - Yuan Qiu; Zhongwei Yan; Jinming Feng; Lijuan Hua; Lijun Fan; Zhen Li; Jun Wang; Cheng Qian (Atmospheric Research, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Association between meteorological factors and varicella incidence: a multicity study in Yunnan Province, China - Hao Wang; Shanjun Huang; Zhaohan Wang; Hua Zhen; Zhuo Li; Wenqi Fan; Menghan Lu; Xin Han; Lanping Du; Meifang Zhao; Yuke Yan; Xinyao Zhang; et al. (Environmental Science and Pollution Research, 2023)

Coseismic slip and deformation mode of the 2022 Mw 6.5 Luding earthquake determined by GPS observation - Hongbao Liang; Yanqiang Wu; Zhigang Shao; Jingwei Li; Yalun Li; Songquan Yi; Fan Yang; Wenquan Zhuang; Hua Wang; Wei Zhan; Changyun Chen (Tectonophysics, 2023)

Tree rings in Tsuga dumosa reveal increasing drought variability in subtropical southwest China over the past two centuries - Yun-Li Yin; Zaw Zaw; Xin-Hua Peng; Hui Zhang; Pei-Li Fu; Wen-Li Wang; Achim Bräuning; Ze-Xin Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

BDE-47 flame retardant exposure induces microglial pyroptosis and cognitive deficits by activating the mtROS-NLRP3 axis via Sirt3 downregulation and is salvaged by honokiol - Dongmei Wang; Quan Yuan; Shuwen Liu; Pu Zhao; Chen Liang; Yilu Ma; Sanqiang Li; Xiaoying Zhu; Xueqin Hao; Jian Shi; Hua Fan (Environmental Pollution, 2023)

Damage detection of bridges subjected to moving load based on domain-adversarial neural network considering measurement and model error - Zhi-Dong Li; Wen-Yu He; Wei-Xin Ren; Yi-Lin Li; Yi-Fan Li; Hua-Cai Cheng (Engineering Structures, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Development and validation of a machine learning model to predict prognosis in HIV-negative cryptococcal meningitis patients: a multicenter study - Junyu Liu; Yaxin Lu; Jia Liu; Jiayin Liang; Qilong Zhang; Hua Li; Xiufeng Zhong; Hui Bu; Zhanhang Wang; Liuxu Fan; Panpan Liang; Jia Xie; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Simultaneous detection of multiple influenza virus subtypes based on microbead-encoded microfluidic chip - Shao-Li Hong; Xuan Wang; Zhong-Hua Bao; Meng-Fan Zhang; Man Tang; Nangang Zhang; Huihong Liu; Zi-Yuan Zhu; Kan Liu; Zhi-Liang Chen; Wei Li (Analytica Chimica Acta, 2023)

A generalized land surface reflectance reconstruction method for aerosol retrieval: Application to the Particulate Observing Scanning Polarimeter (POSP) onboard GaoFen-5 (02) satellite - Zheng Shi; Yisong Xie; Zhengqiang Li; Ying Zhang; Cheng Chen; Linlu Mei; Hua Xu; Haofei Wang; Yang Zheng; Zhenhai Liu; Jin Hong; Mengyao Zhu; et al. (Remote Sensing of Environment, 2023)

Millettia speciosa Champ cellulose-based hydrogel as a novel delivery system for Lactobacillus paracasei: Its relationship to structure, encapsulation and controlled release - Meng-Fan Li; Hua-Ling Cui; Wen-Yong Lou (Carbohydrate Polymers, 2023)

Functional and molecular approaches for studying and controlling microbial communities in anaerobic digestion of organic waste: a review - Nora Dinova; Wei Peng; Mihaela Kirilova-Belouhova; Chao Li; Irina Schneider; Erqi Nie; Ivaylo Yotinov; Haowen Duan; Yovana Todorova; Fan Lü; Hua Zhang; Yana Topalova; et al. (Reviews in Environmental Science and Bio/Technology, 2023)

Engineering performance and microstructure characteristics of natural marine sediment stabilized with quicklime-activated GGBS under different lime proportions - Guang-Hua Cai; Yi-Fan Zhou; Chi Sun Poon; Jiang-Shan Li (Marine Georesources & Geotechnology, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Ordered macroporous carbonous skeletons implanted with dual-phase Co/CoFe nanoparticles for boosting electrocatalytic performance - Jun-Xuan Li; Longlong Fan; Qingfeng Hua; Qinghong Geng; Yingying Zhang; Xiaoli Fan; Lian Ma; Chengming Wang; Wei Zhu; Xiao Feng; Cuiling Li (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Earthworm activities enhance taro production by reducing weed infestation through taro–earthworm coculture - Tao Li; Jie-Qun Fan; Hua-Wei Qian; Ji-Hui Wei; Zhen-Guan Qian; Shui-Liang Guo; Wei-Guang Lv (Agriculture, Ecosystems & Environment, 2023)

Water-lifting and aeration system improves water quality of drinking water reservoirs: Biological mechanism and field application - Liqing Kou; Tinglin Huang; Haihan Zhang; Kai Li; Fengyao Hua; Cheng Huang; Xiang Liu; Fan Si (Journal of Environmental Sciences, 2023)

Heat transfer characteristics of premixed methane-air flame jet impinging on a hemispherical surface - Jinpeng Hua; Jianfeng Pan; Feiyang Li; Baowei Fan; Zhongjia Li; Abiodun Oluwaleke Ojo (Fuel, 2023)

Effect of MOF-derived carbon–nitrogen nanosheets co-doped with nickel and titanium dioxide nanoparticles on hydrogen storage performance of MgH2 - Zhiqiang Lan; Feifan Hong; Weitao Shi; Ruolin Zhao; Renhuan Li; Yi Fan; Haizhen Liu; Wenzheng Zhou; Hua Ning; Jin Guo (Chemical Engineering Journal, 2023)

Subcellular damages of pathogenic fungi combined with gene expression analysis reveals mechanisms that cold plasma controlling apricot disease - Yue Pan; Tingting Li; Caie Wu; Shuangfeng Guo; Gongjian Fan; Xiaojing Li; Dandan Zhou; Xiaowen Hua (Food Bioscience, 2023)

Piezoelectric energy harvesting and dissipating behaviors of polymer-based piezoelectric composites for nanogenerators and dampers - Wenzheng Chen; Qitan Zheng; Yi Ang Lv; Yujie Chen; Qunfu Fan; Xunhuang Zhou; Hua Li; Qili Yu; Hezhou Liu (Chemical Engineering Journal, 2023)

Study on Flow Field Variation in Fracture Channel of Coalfield Fire - Qing-Wei Li; Hui-Pan Fan; Jia-Yu Feng; Li-Feng Ren; Teng Ma; Hao Zhang; Kun-Hua Liu; Yang Xiao (Natural Resources Research, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

A comparison of hydrothermal events and petroleum migration between Ediacaran and lower Cambrian carbonates, Central Sichuan Basin - Kaikai Li; Binran Gong; Xinghe Zhang; Hua Jiang; Junjia Fan; Yineng Tan (Marine and Petroleum Geology, 2023)

Integrated comparative transcriptome and weighted gene co-expression network analysis provide valuable insights into the response mechanisms of crayfish (Procambarus clarkii) to copper stress - Zhanqi Wang; Lianlian Yang; Fan Zhou; Jiapeng Li; Xiaoyin Wu; Xueting Zhong; He Lv; Shaokui Yi; Quanxin Gao; Zi Yang; Pengfei Zhao; Yi Wu; et al. (Journal of Hazardous Materials, 2023)

Molecular behavior and interactions with microbes during anaerobic degradation of bio-derived DOM in waste leachate - Junjie Qiu; Tianqi Li; Fan Lü; Yulong Huang; Chao Li; Hua Zhang; Liming Shao; Pinjing He (Journal of Environmental Sciences, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

Pollutant impacts on bacteria in surface water and sediment: Conventional versus emerging pollutants in Taihu Lake, China - Yifei Li; Chengnuo Zhang; Xiaoxuan Wang; Xiaolin Liao; Qin Zhong; Tao Zhou; Fan Gu; Hua Zou (Environmental Pollution, 2023)

Genome-wide analysis of genetic pleiotropy and causal genes across three age-related ocular disorders - Xueming Yao; Hongxi Yang; Han Han; Xuejing Kou; Yuhan Jiang; Menghan Luo; Yao Zhou; Jianhua Wang; Xutong Fan; Xiaohong Wang; Mulin Jun Li; Hua Yan (Human Genetics, 2023)

Classification of rose petal colors based on optical spectrum and pigment content analyses - Hua Wang; Youwei Fan; Yuan Yang; Hui Zhang; Maofu Li; Pei Sun; Xinzhu Zhang; Zhen Xue; Wanmei Jin (Horticulture, Environment, and Biotechnology, 2023)

Metabolites, gene expression, and gut microbiota profiles suggest the putative mechanisms via which dietary creatine increases the serum taurine and g-ABA contents in Megalobrama amblycephala - Yizhuo Hua; Wangwang Huang; Fan Wang; Zhao Jing; Juntao Li; Qingchao Wang; Yuhua Zhao (Fish Physiology and Biochemistry, 2023)

Accurate and rapid quantification of PD-L1 positive exosomes by a triple-helix molecular probe - Zhichao Fan; Qin Weng; Yingxue Li; Tian Zeng; Junyi Wang; Honglan Zhang; Hua Yu; Yan Dong; Xiang Zhao; Jianjun Li (Analytica Chimica Acta, 2023)

Influence of reservoir parameter variation on the multi-injection well model of the Voronoi fracture - Chang Shuai Shi; Shu Fan; Yan Xin Lv; Xiao Hua Zhu; Quan Gan; Hai Bo Li (Arabian Journal of Geosciences, 2023)

Spatial characterization of HCHO and reapportionment of its secondary sources considering photochemical loss in Taiyuan, China - Jingya Hua; Yang Cui; Lili Guo; Hongyan Li; Jie Fan; Yanan Li; Yonghong Wang; Kankan Liu; Qiusheng He; Xinming Wang (Science of The Total Environment, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

Exploration the role of INHBA in Hu sheep granulosa cells using RNA-Seq - Yongjin Bao; Xiaodan Li; M.A. El-Samahy; Hua Yang; Zhibo Wang; Fan Yang; Xiaolei Yao; Feng Wang (Theriogenology, 2023)

Spread of flushing-generated fecal aerosols in a squat toilet cubicle: Implication for infection risk - Danting Luo; Jiayu Huang; Xiaohong Zheng; Fan Liu; Yuguo Li; Ying Wang; Hua Qian (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Pulsed light improved the shelf life of apricot （after simulated long-distance air transportation） by regulating cell wall metabolism - Xiaowen Hua; Tingting Li; Caie Wu; Dandan Zhou; Gongjian Fan; Xiaojing Li; Kaiping Cong; Zhicheng Yan; Xin Cheng (Postharvest Biology and Technology, 2023)

Unsupervised classification of polarimetric SAR images via SV G p 0 MM with extended variational inference - Ze-Chen Li; Heng-Chao Li; Gui Gao; Ze-Xi Hua; Fan Zhang; Wen Hong (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Occurrence and exposure risk assessment of pesticide residues in green tea samples cultivated in Hangzhou area, China - Ji-cai Fan; Jun An; Ren Ren; Shao-ying Liu; Hua-li He; Gang Zhao (Food Additives & Contaminants Part B-Surveillance, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Substance flow analysis on the leachate DOM molecules along five typical membrane advanced treatment processes - Tianqi Li; Fan Lü; Junjie Qiu; Hua Zhang; Pinjing He (Water Research, 2023)

An angular normalization method for temperature vegetation dryness index (TVDI) in monitoring agricultural drought - Zunjian Bian; J.L. Roujean; Tengyuan Fan; Yadong Dong; Tian Hu; Biao Cao; Hua Li; Yongming Du; Qing Xiao; Qinhuo Liu (Remote Sensing of Environment, 2023)

Genome and transcriptome of Chinese medaka (Oryzias sinensis) and its uses as a model fish for evaluating estrogenicity of surface water - Yue Wang; Jilong Guo; Xiaojing Jia; Xiaozhe Luo; Ying Zhou; Xingtai Mao; Xiaolin Fan; Hongxia Hu; Hua Zhu; Chengxia Jia; Xuan Guo; Lan Cheng; et al. (Environmental Pollution, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Electron exchange capacities of colloidal biochar: Affected by spatial structure distribution instead of particle size - Shasha Li; Fan Lü; Hua Zhang; Liming Shao; Pinjing He (Chemical Engineering Journal, 2023)

Dual-bionic, fluffy, and flame resistant polyamide-imide ultrafine fibers for high-temperature air filtration - Yuezhen Hua; Yuyao Li; Zekai Ji; Wang Cui; Zheng Wu; Jie Fan; Yong Liu (Chemical Engineering Journal, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Production and characterization of novel thermo- and organic solvent–stable keratinase and aminopeptidase from Pseudomonas aeruginosa 4–3 for effective poultry feather degradation - Xiao-Dong Pei; Fan Li; Shi-Yang Yue; Xiao-Ni Huang; Tian-Tian Gao; Dao-Quan Jiao; Cheng-Hua Wang (Environmental Science and Pollution Research, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Idiomarina rhizosphaerae sp. nov. isolated from rhizosphere soil of Kalidium cuspidatum, and reclassification of Idiomarina andamanensis as Pseudidiomarina andamanensis comb. nov., and Idiomarina mangrovi as Pseudidiomarina mangrovi comb. nov - Lu-Fan Li; Lian Xu; Hua-Mei Wei; Ji-Quan Sun (Archives of Microbiology, 2022)

CAF-derived midkine promotes EMT and cisplatin resistance by upregulating lncRNA ST7-AS1 in gastric cancer - Ke-Da Yang; Ying Wang; Fan Zhang; Qing-Ling Li; Bai-Hua Luo; De-Yun Feng; Zhi-Jun Zeng (Molecular and Cellular Biochemistry, 2022)

Temporal-spatial variation, source forensics of PAHs and their derivatives in sediment from Songhua River, Northeastern China - Rashid Mohammed; Zi-Feng Zhang; Ying-Hua Hu; Chao Jiang; Zhi-Qiang He; Wen-Juan Wang; Yi-Fan Li (Environmental Geochemistry and Health, 2022)

Immobilization of Cd2+ and Pb2+ by biomineralization of the carbonate mineralized bacterial consortium JZ1 - Peng Zhang; Xiao-Qiang Liu; Li-yuan Yang; Hua-ze-yu Sheng; An-qi Qian; Ting Fan (Environmental Science and Pollution Research, 2022)

Responses of absorptive root and mycorrhizal colonization of Chinese fir (Cunninghamia lanceolata) to varied environmental conditions - Ying-Chun Liao; Hou-Bao Fan; Liang Li; Xiao-Hua Wei; Hui-Min Wang; Hong-Lang Duan; Wen-Fei Liu; Jia-Li Liu (Plant Ecology, 2022)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

Genome-wide association study of SARS-CoV-2 infection in Chinese population - Jie Fan; Quan-Xin Long; Ji-Hua Ren; Hao Chen; Meng-Meng Li; Zheng Cheng; Juan Chen; Li Zhou; Ai-Long Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

RNA-seq Provides Novel Insights into Response to Acute Salinity Stress in Oriental River Prawn Macrobrachium nipponense - Yaoran Fan; Jianbin Feng; Nan Xie; Feiyue Ling; Zefei Wang; Keyi Ma; Xueming Hua; Jiale Li (Marine Biotechnology, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Anti-hyperglycaemic effect of labdane diterpenes isolated from the rhizome of Amomum maximum Roxb., an edible plant in Southwest China - Chuan-Li Lu; Li-Ning Wang; Ya-Jun Li; Qing-Fei Fan; Qing-Hua Huang; Jun-Jia Chen (Natural Product Research, 2022)

Hypoglycemic and hypolipidemic effects of sugar beet (Beta vulgaris L.) extract on C57BL/KsJ db/db mice - Zhipan Wu; Haitao Gong; Yuhang Shen; Haote Han; Wei Zhu; Jingkui Tian; Hua Fan; Shouxin Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Integrative testing device for investigating the hydro-mechanical behavior of highly expansive clay - Yun-zhi Tan; Fan Peng; Hui Li; Hua-jun Ming; De-an Sun (Arabian Journal of Geosciences, 2022)

Correction to: Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

The in vitro and in vivo anti-inflammatory activities of triterpene saponins from Clematis florida - Na-Na Yang; Yi-Fan Zhang; Hai-Tao Zhang; Xin-Hua Ma; Jin-Huang Shen; Peng Li; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2021)

Halomonas salipaludis sp. nov., isolated from a saline-alkali wetland soil - Juyuan Xing; Qi Gong; Liu Tang; Jiao Li; Hua Fan; Xiaowei Wang; Hongxia Liu; Guishan Zhang; Jinxing Zhu (Archives of Microbiology, 2021)

Monochloropropanediol in edible vegetable oils from Hangzhou market in China: occurrence and exposure risk assessment - Ji-Cai Fan; Hua-li He; Ren Ren; Shu-ting Wang (Food Additives & Contaminants: Part A, 2021)

Efficient and automatic extraction of slope units based on multi-scale segmentation method for landslide assessments - Faming Huang; Siyu Tao; Zhilu Chang; Jinsong Huang; Xuanmei Fan; Shui-Hua Jiang; Wenbin Li (Landslides, 2021)

MiR-590-5p inhibits pathological hypertrophy mediated heart failure by targeting RTN4 - Ping Fan; Likun Zhang; Tianyu Cheng; Jing Wang; Junyun Zhou; Li Zhao; Cuie Hua; Quan Xia (Journal of Molecular Histology, 2021)

Rubus chingii var. suavissimus alleviates high-fat diet-induced lipid metabolism disorder via modulation of the PPARs/SREBP pathway in Syrian golden hamsters - Man-Jing Jiang; Li Li; Wan-Fang Huang; Jian Su; Yao-Hua Li; Xiao-Sheng Qu; Lan-Lan Fan (Journal of Natural Medicines, 2021)

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Somatic embryogenesis of masson pine (Pinus massoniana): initiation, maturation and genetic stability analysis at SSR loci - Xin-Rui Xia; Fan Yang; Xin Ke; You-Mei Chen; Jian-Ren Ye; Li-Hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

RNA-Seq Transcriptome Analysis of the Liver and Brain of the Black Carp (Mylopharyngodon piceus) During Fasting - Ya-Fan Dai; Yu-bang Shen; Shen-Tong Wang; Jia-Hua Zhang; Yu-Hong Su; Sheng-Chen Bao; Xiao-Yan Xu; Jia-Le Li (Marine Biotechnology, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

Deep Placement of Nitrogen Fertilizer Affects Grain Yield, Nitrogen Recovery Efficiency, and Root Characteristics in Direct-Seeded Rice in South China - Yunyan Chen; Pingshan Fan; Zhaowen Mo; Leilei Kong; Hua Tian; Meiyang Duan; Lin Li; Liji Wu; Zaimang Wang; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2021)

Study on Physiological Mechanism of Using Cottonseed Meal to Improve Salt–Alkali Tolerance of Cotton - Hongxiu Ma; Chunmei Meng; Kaixiang Zhang; Kaiyong Wang; Hua Fan; Yingbin Li (Journal of Plant Growth Regulation, 2021)

Etv5 safeguards trophoblast stem cells differentiation from mouse EPSCs by regulating fibroblast growth factor receptor 2 - Kui Zhu; Yuan Liu; Chen Fan; Mengyao Zhang; Hongxia Cao; Xin He; Na Li; Dianfeng Chu; Fang Li; Min Zou; Jinlian Hua; Huayan Wang; et al. (Molecular Biology Reports, 2020)

Straw Incorporation Coupled with Deep Placement of Nitrogen Fertilizer Improved Grain Yield and Nitrogen Use Efficiency in Direct-Seeded Rice - Yunyan Chen; Pingshan Fan; Lin Li; Hua Tian; Umair Ashraf; Zhaowen Mo; Meiyang Duan; Qiantong Wu; Zheng Zhang; Xiangru Tang; Shenggang Pan (Journal of Soil Science and Plant Nutrition, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Determination of phthalate esters in breast milk before and after frozen storage in milk storage bags - Ji-Cai Fan; Ren Ren; Hua-Li He; Quan Jin; Shu-Ting Wang (Food Additives & Contaminants: Part A, 2020)

Somatic embryogenesis in slash pine (Pinus elliottii Engelm): improving initiation of embryogenic tissues and maturation of somatic embryos - Fan Yang; Xin-Rui Xia; Xin Ke; Jianren Ye; Li-hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The molecular mechanisms of copper metabolism and its roles in human diseases - Ji Chen; Yunhui Jiang; Hua Shi; Yougong Peng; Xueying Fan; Chenghua Li (Pflügers Archiv - European Journal of Physiology, 2020)

Correction to: Long-Term Oral Toxicity and Anti-osteoporotic Effect of Sintered Dicalcium Pyrophosphate in Rat Model of Postmenopausal Osteoporosis - Yuh-Feng Tsai; Li-Ho Hsu; Chang-Chin Wu; Wei-Hua Cai; Kai-Chiang Yang; Fang-Yu Fan (Journal of Medical and Biological Engineering, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Characterization of the primate TRIM gene family reveals the recent evolution in primates - Shi Qiu; Hua Liu; Zuoyi Jian; Zhenxin Fan; Sanxu Liu; Jinchuan Xing; Jing Li (Molecular Genetics and Genomics, 2020)

SCFAs induce autophagy in intestinal epithelial cells and relieve colitis by stabilizing HIF-1α - Chao Zhou; Liangzi Li; Teming Li; Lihua Sun; Jiuheng Yin; Haidi Guan; Liucan Wang; Hongbing Zhu; Peng Xu; Xin Fan; Baifa Sheng; Weidong Xiao; et al. (Journal of Molecular Medicine, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

l-Glutamic acid induced the colonization of high-efficiency nitrogen-fixing strain Ac63 (Azotobacter chroococcum) in roots of Amaranthus tricolor - Yi-Fan Wang; Jun-Feng Wang; Zhi-Min Xu; Shao-Hua She; Jun-Qing Yang; Qu-Sheng Li (Plant and Soil, 2020)

A new diterpenoid alkaloid from Aconitum hemsleyanum - Zhi-Hui Luo; Yang Chen; Xin-Yi Sun; Hua Fan; Wei Li; Liang Deng; Tian-Peng Yin (Natural Product Research, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Evaluation of the genetic diversity of mango (Mangifera indica L.) seedling germplasm resources and their potential parents with start codon targeted (SCoT) markers - Li Zhou; Xin-Hua He; Hai-Xia Yu; Mei-Yan Chen; Yan Fan; Xiu-Juan Zhang; Zhong-Bing Fang; Cong Luo (Genetic Resources and Crop Evolution, 2020)

Contribution of skeletal muscular glycine to rapid antidepressant effects of ketamine in an inflammation-induced mouse model of depression - Niannian Huang; Yue Wang; Gaofeng Zhan; Fan Yu; Shan Li; Dongyu Hua; Riyue Jiang; Shiyong Li; Yeshun Wu; Ling Yang; Bin Zhu; Fei Hua; et al. (Psychopharmacology, 2019)

Effects of Modifiers on the Growth, Photosynthesis, and Antioxidant Enzymes of Cotton Under Cadmium Toxicity - MengJie An; HaiJiang Wang; Hua Fan; J. A. Ippolito; Chunmei Meng; Yulian E.; Yingbin Li; Kaiyong Wang; Changzhou Wei (Journal of Plant Growth Regulation, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Detection of 20 phthalate esters in breast milk by GC-MS/MS using QuEChERS extraction method - Ji-Cai Fan; Ren Ren; Quan Jin; Hua-Li He; Shu-Ting Wang (Food Additives & Contaminants: Part A, 2019)

Three BnaIAA7 homologs are involved in auxin/brassinosteroid-mediated plant morphogenesis in rapeseed (Brassica napus L.) - Ming Zheng; Maolong Hu; Hongli Yang; Min Tang; Liang Zhang; Hongfang Liu; Xiaokang Li; Jinglin Liu; Xingchao Sun; Shihang Fan; Jiefu Zhang; William Terzaghi; et al. (Plant Cell Reports, 2019)

Effects of metaxenia on the carbohydrate and mogroside content and related enzyme activities in Siraitia grosvenorii fruit - Zhi-gang Yan; Dong Xiao; Yong-li Xu; Jing Ma; Fan Liu; Long-hua Bai; Xiao-jun Ma (Acta Physiologiae Plantarum, 2019)

Two new steroids with cytotoxicity from the marine sponge Dactylospongia elegans collected from the South China Sea - Jing Li; Zhuo Wang; Fan Yang; Wei-Hua Jiao; Hou-Wen Lin; Shi-Hai Xu (Natural Product Research, 2019)

Novel hepacivirus in Asian house shrew, China - Hua Guo; Chunlin Cai; Bo Wang; Fei Zhuo; Rendi Jiang; Ning Wang; Bei Li; Wei Zhang; Yan Zhu; Yi Fan; Wushen Chen; Weihong Chen; et al. (Science China Life Sciences, 2019)

Bile-ology: from bench to bedside - Li-hua Jin; Zhi-peng Fang; Min-jie Fan; Wen-dong Huang (Journal of Zhejiang University-SCIENCE B, 2019)

Distal Axonal Proteins and Their Related MiRNAs in Cultured Cortical Neurons - Chao Li; Yi Zhang; Albert M. Levin; Bao Yan Fan; Hua Teng; Moleca M. Ghannam; Michael Chopp; Zheng Gang Zhang (Molecular Neurobiology, 2019)

Inheritance patterns of anthocyanins in berry skin and flesh of the interspecific population derived from teinturier grape - Le Guan; Peige Fan; Shao-Hua Li; Zhenchang Liang; Ben-Hong Wu (Euphytica, 2019)

An H-ferritin from the hydrothermal vent shrimp Rimicaris exoculata and its potential role in iron metabolism - Xiao-Li Liu; Sen Ye; Hua-Wei Li; Bo Lu; Yan-Qin Yu; Yu-Peng Fan; Wei-Jun Yang; Jin-Shu Yang (BioMetals, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Relationship between the onset date of the Meiyu and the South Asian anticyclone in April and the related mechanisms - Hua Li; Shengping He; Ke Fan; Huijun Wang (Climate Dynamics, 2019)

Bhargavaea changchunensis sp. nov. isolated from soil in China - Feng-Hua Tian; Dong-Yu Fan; Chen Zhang; Chuan-Wen Jia; Wei Gao; Yu Li; Chang-Tian Li (Archives of Microbiology, 2018)

Comparative analysis of different underlying surfaces using a high-resolution assimilation dataset in semi-arid areas in China - Jinshuai Ruan; Xiaohang Wen; Guangzhou Fan; Deqin Li; Wei Hua; Bingyun Wang; Yi Zhang; Mingjun Zhang; Chao Wang; Lei Wang (Theoretical and Applied Climatology, 2018)

CYP46A1 and the APOEε4 Allele Polymorphisms Correlate with the Risk of Alzheimer’s Disease - Ling Li; Fan Zeng; Yu-Hui Liu; Hui-Yun Li; Shu-Yang Dong; Ze-Yan Peng; Yan-Jiang Wang; Hua-Dong Zhou (Molecular Neurobiology, 2018)

AhR activation protects intestinal epithelial barrier function through regulation of Par-6 - Kun Yu; Yuanhang Ma; Zhicao Zhang; Xin Fan; Teming Li; Liangzi Li; Weidong Xiao; Yujiao Cai; Lihua Sun; Pengyuan Xu; Min Yu; Hua Yang (Journal of Molecular Histology, 2018)

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus - Sai-Juan Xu; Fan Zhang; Li-Juan Wang; Ming-Hua Hao; Xian-jun Yang; Na-na Li; Hong-long Ji; Ping Xu (Apoptosis, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Inflammatory Response Occurs in Veins of Broiler Chickens Treated with a Selenium Deficiency Diet - Changyu Cao; Ruifeng Fan; Menghao Chen; Xiaojing Li; Mengyuan Xing; Fating Zhu; Hua Xue; Kai Wang; Shiwen Xu (Biological Trace Element Research, 2018)

Effects of Fluoride on Surface Structure of Primary Culture Leydig Cells in Mouse - Jian Li; Yan Shi; Hua Fan; Yanyan Li; Yuchen Zhu; Xijun Lin; Jianhai Zhang (Biological Trace Element Research, 2018)

Rapid Detection of Serratia fonticola by TaqMan Quantitative Real-Time PCR Using Primers Targeting the gyrB Gene - Jing Hua Ruan; Wu Jun Wang; Ti Yin Zhang; Quan Yang Bai; Teng Zheng; Zhi Deng Zhang; Li Yun Wu; Yi Fan Huang; Dao Jin Yu (Current Microbiology, 2017)

Identification and sex expression profiling of odorant-binding protein genes in Trichogramma japonicum (Hymenoptera: Trichogrammatidae) using RNA-Seq - Jia-Dong Wu; Zhao-Can Shen; Hai-Qing Hua; Fan Zhang; Yuan-Xi Li (Applied Entomology and Zoology, 2017)

Protective effect of dihydropteridine reductase against oxidative stress is abolished with A278C mutation - Yan-ting Gu; Yan-chun Wang; Hao-jun Zhang; Ting-ting Zhao; Si-fan Sun; Hua Wang; Bin Zhu; Ping Li (Journal of Zhejiang University-SCIENCE B, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Long-Term Oral Toxicity and Anti-osteoporotic Effect of Sintered Dicalcium Pyrophosphate in Rat Model of Postmenopausal Osteoporosis - Yuh-Feng Tsai; Li-Ho Hsu; Chang-Chin Wu; Wei-Hua Cai; Kai-Chiang Yang; Fang-Yu Fan (Journal of Medical and Biological Engineering, 2017)
Sintered dicalcium pyrophosphate (SDCP), a synthetic pyrophosphate analog, has shown potential for the management of osteoporosis. The long-term oral toxicity and anti-osteoporotic effect of SDCP in a postmenopausal osteoporosis rat model were evaluated in this study. SDCP was orally administered to bilateral ovariectomized (OVX) Wistar rats at a dose of 0.75 mg/kg daily for 24 weeks following by 2 weeks of observation. There were no abnormal findings in clinical signs of toxicity, food consumption, body weight, blood examination, necropsy, and histological inspection attributable to the ingestion of SDCP. The serum level of type I collagen fragments, a bone resorption marker, decreased in SDCP-treated rats, and the bone formation markers alkaline phosphatase, osteocalcin, and osteopontin significantly decreased. These findings indicate that the bone turnover rate decreased in SDCP-treated animals. Relative to OVX rats, the increase in serum tartrate-resistant acid phosphatase 5b level represents an increase in bony tissues in the SDCP-treated rats. Histological examinations of distal femoral metaphyses further revealed that the ingestion of SDCP improved the trabecular bone architecture and decreased bone porosity. Analysis of limb bone ashes showed a significant increase in bone mineral content. Our results show that SDCP inhibits bone resorption to restore bone mass in OVX rats without deleterious effects, and therefore that SDCP has potential in the management of osteoporosis.

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

RAS Promotes Proliferation and Resistances to Apoptosis in Meningioma - Chunling Jiang; Tao Song; Jingao Li; Fan Ao; Xiaochang Gong; Yicheng Lu; Chenran Zhang; Liangyu Chen; Yunhui Liu; Hua He; Ouping Huang (Molecular Neurobiology, 2017)

The prevalence and genotype distribution of rotavirus A infection among children with acute gastroenteritis in Kunming, China - Ziqin Dian; Mao Fan; Binghui Wang; Yue Feng; Hao Ji; Shuwei Dong; A-Mei Zhang; Li Liu; Hua Niu; Xueshan Xia (Archives of Virology, 2017)

Genome-wide profiling of genetic variation in Agrobacterium-transformed rice plants - Wen-xu Li; San-ling Wu; Yan-hua Liu; Gu-lei Jin; Hai-jun Zhao; Long-jiang Fan; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Use of mixed solid waste as a soil amendment for saline-sodic soil remediation and oat seedling growth improvement - Yuan Fan; Tian Ge; Yanli Zheng; Hua Li; Fangqin Cheng (Environmental Science and Pollution Research, 2016)

Influence of ginseng cultivation under larch plantations on plant diversity and soil properties in Liaoning Province, Northeast China - Wei-wei Liu; Mou-cheng Liu; Wen-hua Li; Fan-shun Zeng; Yi Qu (Journal of Mountain Science, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Energy-Use Efficiency and Economic Analysis of Sugar Beet Production in China: A Case Study in Xinjiang Province - Fan Hua; Li Yangyang; Fei Cong; Huo Peishu; Wang Kaiyong (Sugar Tech, 2016)

Inhibition effects of high calcium concentration on anaerobic biological treatment of MSW leachate - Yi Xia; Pin-Jing He; Hong-Xia Pu; Fan Lü; Li-Ming Shao; Hua Zhang (Environmental Science and Pollution Research, 2016)

The impacts of migrant workers consumption on energy use and CO2 emissions in China - Jing-Li Fan; Hua Liao; Bao-Jun Tang; Su-Yan Pan; Hao Yu; Yi-Ming Wei (Natural Hazards, 2016)

Enriched Environment Attenuates Surgery-Induced Impairment of Learning, Memory, and Neurogenesis Possibly by Preserving BDNF Expression - Dan Fan; Jun Li; Bin Zheng; Lei Hua; Zhiyi Zuo (Molecular Neurobiology, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Decreased Zn2+ Influx Underlies the Protective Role of Hypoxia in Rat Nucleus Pulposus Cells - Yin Xiao-Fan; Jiang Li-Bo; Ma Yi-Qun; Xu Jun; Gu Hui-Jie; Wu Xu-Hua; Li Xi-Lei; Dong Jian (Biological Trace Element Research, 2015)

A three-channel algorithm for retrieving night-time land surface temperature from MODIS data under thin cirrus clouds - Xiwei Fan; Bo-Hui Tang; Hua Wu; Guangjian Yan; Zhao-Liang Li (International Journal of Remote Sensing, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

A newly isolated Haloalkaliphilic bacterium from middle–late Eocene halite formed in salt lakes in China - Fan-Wei Meng; Xiu-Qiang Wang; Pei Ni; Gunther Kletetschka; Chun-He Yang; Yin-Ping Li; Yong-Hua Yang (Carbonates and Evaporites, 2015)

Effects of semi-lunar tidal cycling on soil CO2 and CH4 emissions: a case study in the Yangtze River estuary, China - Nai-Shun Bu; Jun-Feng Qu; Hua Zhao; Qing-Wu Yan; Bin Zhao; Jing-Lan Fan; Chang-Ming Fang; Gang Li (Wetlands Ecology and Management, 2015)

Duration-dependent regulation of autophagy by isoflurane exposure in aged rats - Zheng-Qian Li; Lun-Xu Li; Na Mo; Yi-Yun Cao; Bolati Kuerban; Yao-Xian Liang; Dong-Sheng Fan; De-Hua Chui; Xiang-Yang Guo (Neuroscience Bulletin, 2015)

Excitotoxicity Induced by Realgar in the Rat Hippocampus: the Involvement of Learning Memory Injury, Dysfunction of Glutamate Metabolism and NMDA Receptors - Tao-guang Huo; Wei-kai Li; Ying-hua Zhang; Jie Yuan; Lan-yue Gao; Yuan Yuan; Hui-lei Yang; Hong Jiang; Gui-fan Sun (Molecular Neurobiology, 2015)

Identification of Two Cucumber Putative Silicon Transporter Genes in Cucumis sativus - Hua-Sen Wang; Chao Yu; Pei-Pei Fan; Bin-Fu Bao; Tao Li; Zhu-Jun Zhu (Journal of Plant Growth Regulation, 2015)

Direct detection, cloning and characterization of a glucoside hydrolase from forest soil - Mei Hua; Shubo Zhao; Lili Zhang; Dongbo Liu; Hongmei Xia; Fan Li; Shan Chen (Biotechnology Letters, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Effects of growth conditions on the production of neurotoxin 2,4-diaminobutyric acid (DAB) in Microcystis aeruginosa and its universal presence in diverse cyanobacteria isolated from freshwater in China - Hua Fan; Jiangbing Qiu; Lin Fan; Aifeng Li (Environmental Science and Pollution Research, 2015)

Genome-wide identification and analysis of the apple (Malus × domestica Borkh.) TIFY gene family - Xiaoqin Li; Xiangjing Yin; Hao Wang; Jun Li; Chunlei Guo; Hua Gao; Yi Zheng; Chonghui Fan; Xiping Wang (Tree Genetics & Genomes, 2015)

Characterization of the morphology and genome of an Escherichia coli podovirus - Yuhui Hua; Xiaoping An; Guangqian Pei; Shasha Li; Wei Wang; Xiaomeng Xu; Huahao Fan; Yong Huang; Zhiyi Zhang; Zhiqiang Mi; Jiankui Chen; Jingyun Li; et al. (Archives of Virology, 2014)

The Association Between Single Nucleotide Polymorphisms of GSK 3β Gene and Sporadic Alzheimer’s Disease in a Cohort of Southern Chinese Han Population - Jing Li; Fan Zeng; Juan Deng; Jie Zhu; Lin Li; Tao Zhang; Juan Liu; Li–Li Zhang; Chang-Yue Gao; Meng Zhang; Zhi-Qiang Xu; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2014)

Effect of temperature on development and reproduction of Proprioseiopsis asetus (Acari: Phytoseiidae) fed on asparagus thrips, Thrips tabaci - Jian Hua Huang; Shoaib Freed; Li Si Wang; Wen Jing Qin; Hong Fan Chen; Hou Guo Qin (Experimental and Applied Acarology, 2014)

Analysis of climate variability in the Manas River Valley, North-Western China (1956–2006) - Fenghua Zhang; Munir A. Hanjra; Fan Hua; Yunqiao Shu; Yuyi Li (Mitigation and Adaptation Strategies for Global Change, 2014)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

Identification and characterization of six cytochrome P450 genes belonging to CYP4 and CYP6 gene families in the silkworm, Bombyx mori - Bing Li; Hua Zhang; Min Ni; Bin-bin Wang; Fan-chi Li; Kai-zhun Xu; Wei-de Shen; Qing-you Xia; Ping Zhao (Molecular Biology Reports, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

First isolation of reticuloendotheliosis virus from mallards in China - Lili Jiang; Xiaoyun Deng; Yulong Gao; Kai Li; Hongliang Chai; Zhaobin Fan; Xiangang Ren; Qi Wang; Lizhou Zhang; Bingling Yun; Chunhong Yin; Yuming Chen; et al. (Archives of Virology, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Synthesis, antibacterial activity, antibacterial mechanism and food applications of ZnO nanoparticles: a review - Lu-E Shi; Zhen-Hua Li; Wei Zheng; Yi-Fan Zhao; Yong-Fang Jin; Zhen-Xing Tang (Food Additives & Contaminants: Part A, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Genome-Wide Phylogenetic Analysis of Stress-Activated Protein Kinase Genes in Rice (OsSAPKs) and Expression Profiling in Response to Xanthomonas oryzae pv. oryzicola Infection - Mei-Rong Xu; Li-Yu Huang; Fan Zhang; Ling-Hua Zhu; Yong-Li Zhou; Zhi-Kang Li (Plant Molecular Biology Reporter, 2013)

QTL mapping for seedling traits under different nitrogen forms in wheat - Jin-jie Sun; Ying Guo; Gui-zhi Zhang; Ming-gang Gao; Guo-hua Zhang; Fan-mei Kong; Yan Zhao; Si-shen Li (Euphytica, 2013)

Effects of breeds and dietary protein levels on the growth performance, energy expenditure and expression of avUCP mRNA in chickens - Qihua Li; Zhiqiang Xu; L. Liu; Hongxin Yu; Hua Rong; Linli Tao; Xi Zhang; Xiaobo Chen; Dahai Gu; Yueyuan Fan; Xiaoqin Li; Changrong Ge; et al. (Molecular Biology Reports, 2013)

Efficient and stable rescue of classical swine fever virus from cloned cDNA using an RNA polymerase II system - Chao Li; Junhua Huang; Yongfeng Li; Fan He; Dan Li; Yuan Sun; Wen Han; Su Li; Hua-Ji Qiu (Archives of Virology, 2013)

Construction and analysis of different expression cDNA libraries in Rehmannia glutinosa plants subjected to continuous cropping - Yan Hui Yang; Zhong Yi Zhang; Hua Min Fan; Yi Dan Zhao; Ming Jie Li; Juan Li; Jun Ying Chen; Wen Xiong Lin; Xin Jian Chen (Acta Physiologiae Plantarum, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

T-2 Toxin Contamination in Grains and Selenium Concentration in Drinking Water and Grains in Kaschin–Beck Disease Endemic Areas of Qinghai Province - Li-Yan Sun; Qiang Li; Fan-Gang Meng; Ying Fu; Zhi-Jun Zhao; Li-Hua Wang (Biological Trace Element Research, 2012)

Traditional Chinese medicines benefit to nonalcoholic fatty liver disease: a systematic review and meta-analysis - Ke-Qing Shi; Yu-Chen Fan; Wen-Yue Liu; Ling-Fei Li; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Meta-analysis of MCP-1 promoter −2518 A/G polymorphism and SLE susceptibility - Ting Liu; Jin-Xia Zhai; Han-Yong Wang; Xing-Hua Wang; Li-Wei Zou; Wen-jing Fan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Heterogeneity in membrane protein genes of porcine epidemic diarrhea viruses isolated in China - Jing-Hui Fan; Yu-Zhu Zuo; Jian-Hui Li; Li-Hua Pei (Virus Genes, 2012)

Differential effects of paraoxonase 1 (PON1) polymorphisms on cancer risk: evidence from 25 published studies - Dai-Hua Fang; Cong-Hai Fan; Qiang Ji; Bo-Xiang Qi; Juan Li; Lu Wang (Molecular Biology Reports, 2012)

Role of mitochondrial pathway in compression-induced apoptosis of nucleus pulposus cells - Fan Ding; Zeng-Wu Shao; Shu-Hua Yang; Qiang Wu; Fei Gao; Li-Ming Xiong (Apoptosis, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Isolation and performance evaluation of halotolerant phosphate solubilizing bacteria from the rhizospheric soils of historic Dagong Brine Well in China - Wen-liang Xiang; Hua-zhong Liang; Sen Liu; Fan Luo; Jie Tang; Ming-yuan Li; Zhen-ming Che (World Journal of Microbiology and Biotechnology, 2011)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Experimental Pathogenicity of a Clinical Isolate of Trichosporon dermatis in a Murine Model - Ying-Ping Lin; Yan-Ping Yang; Wen-Ming Huang; Yong-Hua Chen; Shun-Fan Li; Yi-Ming Fan (Mycopathologia, 2011)

Interleukin-6, but Not Soluble Adhesion Molecules, Predicts a Subsequent Mortality from Cardiovascular Disease in Patients with Acute ST-Segment Elevation Myocardial Infarction - Zhen-Xing Fan; Qi Hua; Yin-Ping Li; Rong-Kun Liu; Zheng Yang (Cell Biochemistry and Biophysics, 2011)

OSL chronology of sand deposits and climate change of last 18 ka in Gurbantunggut Desert, northwest China - Sheng‐Hua Li; Anchuan Fan (Journal of Quaternary Science, 2011)
The development of the Gurbantunggut Desert is mainly controlled by the Westerly wind, and at present has little influence from Indian and Southeast Asian monsoons. A combined study using optically stimulated luminescence (OSL) dating, ground‐penetrating radar (GPR) surveys and climatic proxies analysis was carried out in the southern part of the desert. The chronology extends back to 18 ka and is constructed based on 16 OSL ages from boreholes in the linear dune body and the inter‐dune area. The chronology suggests that sand deposition in the last 18 ka experienced two rapid accumulation phases at 11 and 2.5 ka ago which were also evident from the GPR surveys. These periods relate to increased aridity in the region. Five climate phases are identified from the last 18 ka, based on the OSL chronology and climatic proxy analysis with grain size and magnetic susceptibility measurements. The deglacial period (18.3–10.4 ka) is characterized by climate instability and possible glacial melting events. The Holocene Optimum peaked 8.5 ka and terminated 3.6 ka ago, when the regional climate became arid. OSL samples from the dune body cluster around 2.5 ka, which indicates rapid advance/extension of dune bodies at this time. Copyright © 2011 John Wiley & Sons, Ltd.

Environmental Lead Exposure Among Children in Chengdu, China, 2007–2009 - Hua Shi; Yong-mei Jiang; Jia-yuan Li; Fang Liu; Hong Wang; Fan Yu; Hui Yang (Biological Trace Element Research, 2011)

Naturalization of alien plants in China - Hua Jiang; Qiang Fan; Jin-Tian Li; Shi Shi; Shao-Peng Li; Wen-Bo Liao; Wen-Sheng Shu (Biodiversity and Conservation, 2011)

Inhibition of Hydrogen Sulfide Generation Contributes to 1-Methy-4-Phenylpyridinium Ion-Induced Neurotoxicity - Xiao-Qing Tang; Li-Li Fan; Yu-Juan Li; Xin-Tian Shen; Yuan-Yuan Zhuan; Jian-Qin He; Jin-Hua Xu; Bi Hu; Yuan-Jian Li (Neurotoxicity Research, 2011)

Estrogen modulation of peripheral pain signal transduction: involvement of P2X3 receptors - Bei Ma; Li-hua Yu; Juan Fan; Binhai Cong; Ping He; Xin Ni; Geoffrey Burnstock (Purinergic Signalling, 2011)

Metabolomics study on the synergistic interaction between Salvia miltiorrhiza and Lignum dalbergiae odoriferae used as ‘Jun-Shi’ herbs in a S. miltiorrhiza recipe - Shi-Xiang Wang; Kai Luo; Jing Liang; Fei Fan; Hua Li; Jian-Bin Zheng; Xiao-Hui Zheng (Medicinal Chemistry Research, 2011)

The −159C/T polymorphism in the CD14 gene and the risk of asthma: a meta-analysis - Yonggang Zhang; Can Tian; Jie Zhang; Xiaobo Li; Hua Wan; Chao He; Liang Guo; Quocuo Meilang; Chunhong Peng; Lina Duo; Jin Huang; Hong Fan (Immunogenetics, 2011)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Notch signaling maintains proliferation and survival of the HL60 human promyelocytic leukemia cell line and promotes the phosphorylation of the Rb protein - Guo-Hui Li; Yu-Zhen Fan; Xiao-Wei Liu; Bing-Fang Zhang; Dan-Dan Yin; Fei He; Si-Yong Huang; Zhi-Jie Kang; Heng Xu; Qiang Liu; Yan-Lan Wu; Xiao-Li Niu; et al. (Molecular and Cellular Biochemistry, 2010)

Effects of sevoflurane preconditioning and postconditioning on rat myocardial stunning in ischemic reperfusion injury - An-lu Dai; Li-hua Fan; Feng-jiang Zhang; Mei-juan Yang; Jing Yu; Jun-kuan Wang; Tao Fang; Gang Chen; Li-na Yu; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

The effects of CYP2C9 and CYP2C19 genetic polymorphisms on the pharmacokinetics and pharmacodynamics of glipizide in Chinese subjects - Bo Tan; Yi-Fan Zhang; Xiao-Yan Chen; Xiao-Hua Zhao; Guo-Xin Li; Da-Fang Zhong (European Journal of Clinical Pharmacology, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Assessment of antifungal effects of a novel compound from Burkholderia cepacia against Fusarium solani by fluorescent staining - Xin Li; Chun-Shan Quan; Hui-Ying Yu; Jian-Hua Wang; Sheng-Di Fan (World Journal of Microbiology and Biotechnology, 2009)

Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2008)

Microsatellite Analysis of Genetic Variation and Population Genetic Differentiation in Autotetraploid and Diploid Rice - Li Luan; Xing Wang; Wen-Bo Long; Yu-Hua Liu; Sheng-Bin Tu; Zhan-Peng Zhao; Fan-Lun Kong; Mao-Qun Yu (Biochemical Genetics, 2008)

Physical mapping and identification of a candidate for the leaf rust resistance gene Lr1 of wheat - Ji-Wen Qiu; Anita Christina Schürch; Nabila Yahiaoui; Ling-Li Dong; Hua-Jie Fan; Zhong-Juan Zhang; Beat Keller; Hong-Qing Ling (Theoretical and Applied Genetics, 2007)

Zinc adsorption and desorption characteristics in root cell wall involving zinc hyperaccumulation in Sedum alfredii Hance - Ting-qiang Li; Xiao-e Yang; Fan-hua Meng; Ling-li Lu (Journal of Zhejiang University-SCIENCE B, 2007)

Inheritance of sugars and acids in berries of grape (Vitis vinifera L.) - Huai-Feng Liu; Ben-Hong Wu; Pei-Ge Fan; Hai-Ying Xu; Shao-Hua Li (Euphytica, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Soil microbial biomass as affected by non-flooded plastic mulching cultivation in rice - Yong-Shan Li; Liang-Huan Wu; Xing-Hua Lu; Li-Mei Zhao; Qiao-Lan Fan; Fu-Suo Zhang (Biology and Fertility of Soils, 2006)

Expression of cysteine sulfinate decarboxylase (CSD) in male reproductive organs of mice - Jian Hua Li; Ya Qin Ling; Jing Jing Fan; Xiao Ping Zhang; Sheng Cui (Histochemistry and Cell Biology, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Induced Activity of Superoxide Dismutase and Peroxidase of in vitro Plants by Low Concentrations of Ethanol - Xiu-Qing Li; Shi-Hua Li; De-Fu Chen; Fan-Rui Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

RS and GIS-based forest fire risk zone mapping in da hinggan mountains - Hai-wei Yin; Fan-hua Kong; Xiu-zhen Li (Chinese Geographical Science, 2004)

IR spectroelectrochemical study of the binding of carbon monoxide to the active site of Desulfovibrio fructosovorans Ni-Fe hydrogenase - Antonio L. De Lacey; Christian Stadler; Victor M. Fernandez; Claude E. Hatchikian; Hua-Jun Fan; Shuhua Li; Michael B. Hall (JBIC Journal of Biological Inorganic Chemistry, 2002)